2000
DOI: 10.1111/j.1365-2141.2000.02444.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined defect in membrane expression and activation of platelet GPIIb–IIIa complex without primary sequence abnormalities in myeloproliferative disease

Abstract: Summary. Defects in glycoprotein (GP)IIb±IIIa or in its activation may cause abnormal platelet aggregation and a bleeding diathesis. We report studies in a 67-year-old man with a myeloproliferative disease and markedly abnormal platelet responses. By flow cytometry, platelet binding of two complex-specific anti-GPIIb±IIIa monoclonal antibodies (mAbs), A2A9 and 10E5, was ,50% of normal. An enzyme-linked immunosorbent assay (ELISA) using immobilized kistrin showed 18% of normal membrane GPIIb±IIIa complex. By im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 35 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…These platelets are active, but they still circulate in blood and they neither form aggregates with other platelets nor adhere to vascular lesions [19]. Various studies demonstrated that The values given are as median (range).…”
Section: Discussionmentioning
confidence: 99%
“…These platelets are active, but they still circulate in blood and they neither form aggregates with other platelets nor adhere to vascular lesions [19]. Various studies demonstrated that The values given are as median (range).…”
Section: Discussionmentioning
confidence: 99%